Multicore software engineering, performance, and tools : International Conference, MUSEPAT 2013, St. Petersburg, Russia, August 19-20, 2013. Proceedings - Farchi, Eitan; Lourenço, Joao M. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the International Conference on Multiscore Software Engineering, Performance, and Tools, MUSEPAT 2013, held in Saint Petersburg, Russia, in August 2013. The 9 revised papers were carefully reviewed and selected from 25 submissions. The accepted papers are organized into three main sessions and cover topics such as software engineering for multicore systems; specification, modeling and design; programing models, languages, compiler techniques and development tools; verification, testing, analysis, debugging and performance tuning, security testing; software maintenance and evolution; multicore software issues in scientific computing, embedded and mobile systems; energy-efficient computing as well as experience reports.